Avaliação mitocondrial em células mononucleares periféricas caninas infectadas com o vírus da cinomose - Agostinho, Sabrina Donatoni [UNESP] (2013)
itochondrial dysfunction is associated with the manifestation and origin of diseases and disorders. The new paradigm complements the current mitochondrial dogma, whereby molecules present on or inside the mitochondria may act as immune regulators in response to stress or pathogens. Canine distemper virus infection (CDV) is responsible to immunosuppressive stage when the virus replicates among immune cells. For this purpose, canine peripheral blood mononuclear cells (PBMC) collected from healthy dogs were cultured and infected by CDV vaccine strain (Onderstepoort) and after 24 h post-infection (p.i.) superoxide dismutase (SOD1), antioxidant like protein 1 (AOP-1) and heat shock protein 70 (Hsp-70) enzymes were search in PBMC by immunofluorescence. The expression of mRNA of respective genes was performed in infected and uninfected canine PBMC at 24 h post-infection by real time polymerase chain reaction. Mitochondrial dysfunction was evaluated by the use of MitoTracker™Green and JC-1 probes at the same post-infection time. The vaccine strain induced loss of PBMC viability in more than 80% of infected cells in comparison to control group (p<0.001) at 24h post-infection. The mitochondrial membrane permeability (Δψ) searched by MitoTracker™ Green and JC-1 probes revealed an increase of Δψ in the CDV + group (p<0.0012) in comparison to uninfected PBMC. In contrast, the expression of mRNA of AOP-1 and SOD 1 were considered higher, whereas the Hsp-70 has no difference in its expression between CDV+ and CDV- groups. PBMC infected by CDV increased AOP-1 and SOD1 gene transcription, an antioxidant cell defense, concomitant to a reduce level of PBMC viability. The viral replication also seems to regulate mitochondrial function by modify the membrane potential. However, at this point, host cells have developed an defense producing mediators related to protect against oxidative insult. This is the first...